2020
DOI: 10.1111/odi.13672
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of the deubiquitinase cylindromatosis (CYLD) on inflammatory responses in human gingival fibroblasts

Abstract: Objective Experiments were performed to evaluate CYLD expression in human gingival tissue samples and to examine the effects of CYLD on inflammatory responses in lipopolysaccharide (LPS)‐ or TNF‐α‐stimulated human gingival fibroblasts (HGFs). Methods Immunohistochemistry for CYLD and p65 expression was performed with healthy and inflamed gingival tissue samples. siRNA was used to knock down the expression of CYLD in HGFs. Upon LPS or TNF‐α stimulation, NF‐κB activation was detected in control and CYLD‐knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Similarly, western blotting data also showed that the protein level of CYLD had no obvious change in the presence of LPS or TNF-α. These ndings are in line with our previous study [4]. In contrast, several early reports indicated that CYLD expression was upregulated by LPS or TNF-α treatment [28][29][30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, western blotting data also showed that the protein level of CYLD had no obvious change in the presence of LPS or TNF-α. These ndings are in line with our previous study [4]. In contrast, several early reports indicated that CYLD expression was upregulated by LPS or TNF-α treatment [28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…Then these samples were processed to para n blocks and sectioned at 5 µm. Immunohistochemical study was undertaken as previously described using a commercial immunohistochemistry kit [4]. Anti-CYLD (1:400), anti-A20…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Then these samples were processed to paraffin blocks and sectioned at 5 µm. Immunohistochemical study was undertaken as previously described using a commercial immunohistochemistry kit [4]. Anti-CYLD (1:400), anti-A20 (1:400) and anti-OTULIN (1:400,) antibodies were applied in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitin, a protein containing 76 amino acids, has an essential role in variety of biological processes [1-4]. Ubiquitination is a critical post-translational protein modification, performed by specific ubiquitin enzymes [5, 6].…”
Section: Introductionmentioning
confidence: 99%